trigonometry question
Attachments:
![](https://hi-static.z-dn.net/files/d91/05093c843eb6012b0e43e0f842582c20.jpg)
Answers
Answered by
2
1+sinA/cosA = cosA/1-sinA
L.H.S
=1+sinA/cosA
=cosA(secA+tanA)/{(1-sinA)[(cosA(1+sinA)/(1-sinA)(1+sinA)]}
=cosA(secA+tanA)/(1-sinA)(secA+tanA)
=cosA/1-sinA
=R.H.S
L.H.S
=1+sinA/cosA
=cosA(secA+tanA)/{(1-sinA)[(cosA(1+sinA)/(1-sinA)(1+sinA)]}
=cosA(secA+tanA)/(1-sinA)(secA+tanA)
=cosA/1-sinA
=R.H.S
Similar questions
Social Sciences,
8 months ago
Computer Science,
8 months ago
Social Sciences,
1 year ago
Math,
1 year ago
Math,
1 year ago